Assessment of Phytochemical Constituents, Antimicrobial Activity, Impurity and Heavy Metal Content of Gynura nepalensis (Bangladesh Pharmaceutical Journal, 2024)
This study explores the multifaceted area of herbal medicine, focusing on Gynura nepalensis, a medicinal plant. The qualitative analyses confirmed the presence of alkaloids, glycosides, phenols, tannins, flavonoids, protein-amino acids, saponins, and carbohydrates. Terpenoids and resin were apparently missing. The antimicrobial activity of the plant extract was assessed and it revealed dose-dependent efficacy against microbial growth. Additionally, the study scrutinized the total ash content, suggesting a moderate level of impurity, and evaluated the heavy metal concentration, finding it well below acceptable limits. Overall, the findings establish the promising role of Gynura nepalensis in natural medicine, urging further investigations and potential applications in integrated healthcare.Bangladesh Pharmaceutical Journal 27(2): 193-200, 2024 (July)